Social status, chaste widowhood, and trends in marital age gaps in post-Imjin Korea, 1606-1630 - Han, Sangwoo; Lee, Byung Ho (International Journal of Asian Studies, 2025)
This study investigates the impact of warfare on nuptial patterns, focusing on the trends and characteristics of age differences within marriage. Specifically, it explores the socio-demographic outcomes of the Imjin War (1592-1598) and post-war reconstruction in Korea, using the earliest extant Chosǒn household registers, compiled between 1606 and 1630. Individual-level microdata were derived involving 2,336 married couples based on 11,749 entries in these registers, covering four administrative districts located in the southeastern region of the Korean peninsula severely devastated by the war. Factors such as status, property, warfare, social practices, and legal regulations influenced spousal age differences. First, social rank and family wealth played pivotal roles, with age gaps widening as a husband's socio-economic status increased. Second, females born after 1580, whose first marriages were affected by the Imjin War and post-war circumstances, experienced an average marital age gap of about ten years. Third, this effect was further complicated by the imposition of socio-legal rules on remarriage; that is, the yangban entailed a pronounced age difference owing to the Neo-Confucian norm of chaste widowhood. This study enriches the understanding of historical marriage customs in Korea and offers insights for studies on age disparity in marriage.
Keywords: chaste widowhood; Chosǒn society; historical demography; household register; Imjin War; marital age gap